ANALISIS CITRA MEREK DAN STRATEGI HARGA DALAM KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI DI PT LAUTAN BERLIAN UTAMA MOTOR CABANG JAKARTA BARAT - Ningsih, Dewi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to determine the influence of brand image and price on purchasing decisions for Mitsubishi passenger cars at PT Lautan Berlian Utama Motor West Jakarta Branch, both partially and simultaneously. This research is descriptive quantitative with an associative approach. Sampling was taken using purposive sampling technique. The population in this study are people who have purchased Mitsubishi passenger cars in residential areas in West Jakarta and its surroundings, including the Depok, Bogor, Bekasi, Tangerang areas. The ancient Rao sample used in this research was 96 respondents. Data collection techniques using observation, questionnaires, data analysis techniques using validity tests, reliability tests, classical assumption tests, linear regression tests, correlation coefficient tests, coefficient of determination tests, hypothesis tests, t tests and f tests with the help of SPSS Version 26 software. The research results show that (1) Brand Image influences purchasing decisions with the regression equation Y=7.081=0.789X1. The correlation coefficient value is 0.837, the coefficient of determination value is 0.700, which has a significant effect on purchasing decisions with a calculated t result of 14.824 > t table 1.986. with a significance level of 0.000 < 0.05. (2) Price influences purchasing decisions with the regression equation Y = 3.524+1.073 .05. (3) Brand Image and Price influence purchasing decisions with the regression equation Y = 1.055+0.420X1+0.694X2, correlation coefficient value of 0.931, determination coefficient value of 0.867, significant influence on purchasing decisions with the result Fcount 302,881 > Ftable 3.094 with a significance of 0.000 < 0.05, then in this study Ha is acceptable.